Severe COVID-19 and long COVID in a 31-year-old woman with incontinentia pigmenti: A case report - Sylvie Rheault (SAGE Publishing, 2021)
Incontinentia pigmenti is a rare genetic disease affecting the skin, microvasculature, and central nervous system, in which a hyperactive inflammatory response is observed. Due to the inflammatory phase of COVID-19 and associated cytokine storm, infection with SARS-CoV-2 in individuals with incontinentia pigmenti is a concern. Furthermore, type I interferon autoantibodies are found in life-threatening COVID-19 pneumonia and in 25% of individuals with incontinentia pigmenti. The present case report describes a 31-year-old Caucasian woman with incontinentia pigmenti and severe COVID-19. She was hospitalized for oxygen therapy, intravenous antibiotics, and corticosteroids. Eight months later, she is still symptomatic. To our knowledge, she is the first reported case of long COVID in incontinentia pigmenti. Increased autoimmunity may be implicated in both incontinentia pigmenti and long COVID. Pending evidence-based guidelines, COVID-protective measures including vaccination should be recommended to all patients with incontinentia pigmenti. Specific interferon therapy may be considered along with usual COVID treatment.